2020
DOI: 10.33225/jbse/20.19.467
|View full text |Cite
|
Sign up to set email alerts
|

Higher and Lower-Order Thinking Skills: The Case of Chemistry Revisited

Abstract: This work analyses students’ failure in the 2019 Nationwide Chemistry Examination in Greece, which concerns secondary education graduates, competing for admission to higher education Greek institutions. The distinction of thinking skills into higher and lower order (HOTS and LOTS) is used as a theoretical tool for this analysis. The examination included several questions that contained HOTS elements that had been unusual in previous examinations. This led to a decrease in overall student performance but better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
(26 reference statements)
1
5
0
1
Order By: Relevance
“…The research results support Arase et al (2016) and Vejian et al (2016), who suggested that creative school climate would cultivate creative behaviour and interactive work among school stakeholders including teachers and learners. The research results prove the claim by Tsaparlis (2020), which states that several education processes are required to enhance science students' HOTs.…”
Section: Discussionsupporting
confidence: 74%
“…The research results support Arase et al (2016) and Vejian et al (2016), who suggested that creative school climate would cultivate creative behaviour and interactive work among school stakeholders including teachers and learners. The research results prove the claim by Tsaparlis (2020), which states that several education processes are required to enhance science students' HOTs.…”
Section: Discussionsupporting
confidence: 74%
“…In general, there is a tendency of giving a paramount importance and special attention to the knowledge and remembering domains (Tikhonova & Kudinova, 2015 ; Tsaparlis, 2020 ). According to Krathwohl ( 2002 ), knowledge and comprehension are frequently considered the foundation to all the other education objectives (Chmielewska & Gilanyi, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The organization for Economic Co-operation and Development (OECD) highlighted one of the elements behind Indonesia's lagging as a focus on Lower Order Thinking Skills (LOTS) in the learning process. With this style of teaching and learning, there is no systematic strategy for strengthening minds in the 21st century (Barut & Wijaya, 2021;Qasrawi & Beniabdelrahman, 2020;Tsaparlis, 2020). Teaching and learning activities which are increasingly dominated by explanations from teachers make learning boring, one-way, and less able to create ways that educate and empower students' learning abilities to discuss, conduct case surgery, solve the problem, experiment, observe, etc.…”
Section: Introductionmentioning
confidence: 99%